Lead fluxes and 206Pb/207Pb isotope ratios in rime and snow collected at remote mountain-top locations (Czech Republic, Central Europe): Patterns and sources. (October 2016) - Cimova, Nikoleta; Novak, Martin; Chrastny, Vladislav; Curik, Jan; Veselovsky, Frantisek; Blaha, Vladimir; Prechova, Eva; Pasava, Jan; Houskova, Marie; Bohdalkova, Leona; Stepanova, Marketa; Mikova, Jitka; et al.
Abstract: During three winter seasons (2009–2011), Pb concentrations were measured in precipitation at 10 high-elevation sites in the Czech Republic, close to the borders with Austria, Germany, Poland, and Slovakia. Soluble and insoluble Pb forms were quantified in snow (vertical deposition), and rime (horizontal deposition). The objective was to compare Pb input fluxes into ecosystems via vertical and horizontal deposition, and to identify the residual Pb pollution sources in an era of rapidly decreasing industrial pollution. Lead soluble in diluted HNO3 made up 96% of total Pb deposition, with the remaining 4% Pb bound mainly in silicates. Three times higher concentrations of soluble Pb in rime than in snow, and 2.5 times higher concentrations of insoluble Pb in rime than in snow were associated with slightly different Pb isotope ratios. On average, the 206 Pb/ 207 Pb ratios in rime were higher than those in snow. Higher mean 206 Pb/ 207 Pb ratios of insoluble Pb (1.175) than in soluble Pb (1.165) may indicate an increasing role of geogenic Pb in recent atmospheric deposition. A distinct reversal to more radiogenic 206 Pb/ 207 Pb ratios in snow and rime in 2010, compared to literature data from rain-fed Sphagnum peatlands (1800–2000 A.D. ), documented a recent decrease in anthropogenic Pb in the atmosphere of Central Europe. Since the early 1980s, Pb concentrations in snow decreased 18 times in the rural south of the Czech Republic, but only twice in the industrial north of the Czech Republic. Isotope signatures indicated that Pb in today's atmospheric deposition is mainly derived from Mesozoic ores mined/processed in Poland and coal combustion in the Czech Republic and Poland. Highlights: Pb concentration in rime is 3 times higher than in snow, showing a different origin. Today, Pb in deposition is more radiogenic than Pb buried in peat around 1800 AD. 206 Pb/ 207 Pb in the insoluble Pb fraction is higher than in the soluble fraction. Since 1983, Pb deposition in rural areas decreased 18 times. Over the same period of time, Pb deposition in industrial areas decreased only twice.